Dinamika Kehidupan Sosial, Politik Dan Budaya Sebagai Salah Satu Sebab Munculnya Fungsi Seni Sebagai Media Penyadaran - Zarkasi, Much. Sofwan (Institut Seni Indoensia Surakarta, 2010)
A paper titled dynamicization Social Life, Politics and Culture Play a Role as One For The emergence of Function of Art For the Media Awareness, describes the role of social life which affect the life and artistic development, especially the emergence of bentukl art that serves as a social awareness. Cultural and social development in a community group from the backwards will bring changes to all fields of politics, economics, art and culture itself. Community needs to grow and expand along with the awareness of individuals or the community in understanding life. Art is the one that felt the changes. The products or works of art created as a counterweight and a response will be the condition of the existing reality. The function of art became more varied, according to the understanding and awareness of its presence.This paper concludes; con-clude that a development of cultural, social, political, economic, will affect the dynamic role of art or artistic function. The effect was so strong because of environmental conditions will affect the human mind or society in it. Art as a product of society must be related to the functions of his presence in the environment and the arts have the power or the power transformation can be flexible and meaningful presence in social life. One of them is an art as a medium of awareness, where the presence of works of art based on awareness of partiality on a commitment to humanitarian and mission aware-ness through art rather than as a mouthpiece of propaganda that is not berestetika, but shared learning space for social transformation that contain aesthetic values.This artwork is also a form of expression or the response of the community in this manner can the artist or the general public towards social environmental conditions that may occur injustice, and this fact must be disclosed. Â With the presence of works of art that has a function as a medium of awareness is expected to occur active communication related to the social reality which is disclosed in the message works. Creators and connoisseurs of art could be more touched and try to understand social reality or the reality that exists, which eventually is expected to show a change for the better.Â Keywords: art, Function of Art, Media Awareness